Unveiling the Role Displayed by Penicillium digitatum PdMut3 Transcription Factor in Pathogen–Fruit Interaction - De-Ramón-Carbonell, Marta; Sánchez-Torres, Paloma (MDPI, 2021)
Zn2Cys6 transcription factors are unique to fungi and are involved in different regulatory functions. In this study, we have identified the Penicillium digitatum PdMut3 gene, which encodes a putative Zn (II) 2Cys6 DNA-binding protein. Elimination of PdMut3 in Pd1 strain caused increased virulence during citrus infection. The transcription of the PdMut3 gene showed a higher expression rate during fungal growth and less transcription during fruit infection. Furthermore, the deletion of the gene in the wild-type isolate of P. digitatum did not produce any modification of the sensitivity to different fungicides, indicating that the gene is not associated with resistance to fungicides. In contrast, PdMut3 null mutants showed a reduction in growth in minimal media, which was associated with severe alterations in conidiophore development and morphological alterations of the hyphae. Mutants showed greater sensitivity to compounds that interfere with the cell wall and an invasive growth block. Thus, PdMut3 might have an indirect role in fungi virulence through metabolism and peroxisomes development.